2015
DOI: 10.3168/jds.2014-9143
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian regression models outperform partial least squares methods for predicting milk components and technological properties using infrared spectral data

Abstract: The aim of this study was to assess the performance of Bayesian models commonly used for genomic selection to predict “difficult-to-predict” dairy traits, such as milk fatty acid (FA) expressed as percentage of total fatty acids, and technological properties, such as fresh cheese yield and protein recovery, using Fourier-transform infrared (FTIR) spectral data. Our main hypothesis was that Bayesian models that can estimate shrinkage and perform variable selection may improve our ability to predict FA traits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 49 publications
11
105
2
1
Order By: Relevance
“…The heritability estimates reported in these GC-based studies (Bobe et al, 2008;Garnsworthy et al, 2010;Bilal et al, 2014) are comparable to those found in the current paper or somewhat higher (Stoop et al, 2008;Schennink et al, 2008). In contrast, the results from studies based on FTIR predictions (Soyeurt et al, 2007;Bastin et al, 2011Bastin et al, , 2013 have commonly been expressed in terms of the weight of a single fatty acid or group of fatty acids per unit of milk (kg or L) due to the low accuracy of FTIR-based predictions of milk fat content (Ferragina et al, 2015). Data expressed as weight of single or groups of fatty acids per unit of milk would produce heritability estimates for fatty acids similar to those of the milk fat content and often greater than those found for proportion of individual fatty acids on total fatty acid content, as in the current and other GC-based experiments.…”
Section: Heritability and Herd-date Effect For Milk Fatty Acid Profilesupporting
confidence: 69%
“…The heritability estimates reported in these GC-based studies (Bobe et al, 2008;Garnsworthy et al, 2010;Bilal et al, 2014) are comparable to those found in the current paper or somewhat higher (Stoop et al, 2008;Schennink et al, 2008). In contrast, the results from studies based on FTIR predictions (Soyeurt et al, 2007;Bastin et al, 2011Bastin et al, , 2013 have commonly been expressed in terms of the weight of a single fatty acid or group of fatty acids per unit of milk (kg or L) due to the low accuracy of FTIR-based predictions of milk fat content (Ferragina et al, 2015). Data expressed as weight of single or groups of fatty acids per unit of milk would produce heritability estimates for fatty acids similar to those of the milk fat content and often greater than those found for proportion of individual fatty acids on total fatty acid content, as in the current and other GC-based experiments.…”
Section: Heritability and Herd-date Effect For Milk Fatty Acid Profilesupporting
confidence: 69%
“…In the sector of the wavenumbers 2,862 to 3,000 cm −1 , several contiguous heritability peaks appear that are well defined in third and later months of lactation. This region has been associated with fat yield (e.g., Bittante and Cecchinato, 2013) and Fat% (e.g., Wang and Bovenhuis, 2018) and with specific fatty acids [e.g., palmitic (C16:0); Ferragina et al, 2015]. Interestingly, the same wavenumbers that were characterized by high heritability estimates in mo 3 to 4 also had very low estimated heritabilities in the first month of the lactation (Figure 3).…”
Section: Discussionmentioning
confidence: 96%
“…Although breeding values for CY and REC have been obtained from direct measures of phenotypes in experimental studies (Bittante et al, 2013a), selection strategies based on direct measures of CY and REC would be very hard to implement. High throughput (potentially, hundreds of samples per hour), ease of use, and reduced cost of analysis make Fourier transform infrared (FTIR) spectroscopy a promising alternative for the assessment of CY and REC at the population level Ferragina et al, 2015).…”
Section: Retention Of Water In Cheese and Cymentioning
confidence: 99%